(3EOGQI GdCYeGd hJMOjGJ GdbQf GdMGOj hGdYTQjf (B/s - (3MSf, Cejf YHO GdYRjRs ((3GdbGgQI(B: s (3OGQ bHGA ddWHGYI hGdfTQ hGdJhRjY(B, s, 2001)
(3JWhQ GdacQ GdEOGQj(B- (3GdYedjI GdEOGQjI(B- (3GdefXeI hGdHjFI GdJcfhdhLjG(B- (3GdJNjWjW hGdEOGQI GdESJQGJjLjI(B- (3GdJfXje(B- (3GdbjGOI(B- (3EJNGP GdbQGQGJ GdEOGQjI(B- (3GdEJUGdGJ GdEOGQjI(B- (3GdQbGHI GdEOGQjI(B- (3EOGQI GdJZjQ aj GdefXeGJ(B- (3GdJfejI GdEOGQjI hCgejJgG(B- (3GdEOGQI GdOhdjI(B- (3EOGQI GdCYeGd aj GdbQf GdMGOj hGdYTQhfs
Keywords: (3GJNGP GdbQGQGJs; (3EOGQI GdCYeGds